OPTIMALISASI POTENSI UMKM DAN INDUSTRI KREATIF PAREPARE MELALUI PELATIHAN PEMASARAN DIGITAL DAN APLIKASI C-COMMERCE - Tunnisa, Khaera; Yulianadewi, Ina; Mar’atuttahirah, Mar’atuttahirah; Palaloi, Rahmat Eka Putra R; Ramadhan, Syam Syahru; Ashilah, Aspiani Putri; Hikma, Nurul (Jurnal AbdiMas Nusa Mandiri, 2026)
This Community Service activity aims to improve the digital capacity and competitiveness of the Kerang Indah Parepare MSME, which processes sea shell waste into economically valuable crafts based on Circular Economy principles. Initial analysis indicated that the partners' main problems included limited product innovation, the lack of structured business records, and low utilization of digital marketing. To address these issues, the team conducted Business Model Canvas training, optimized Google My Business, utilized WhatsApp Business and Facebook Ads, and implemented the C-Commerce application as a digital catalog and record-keeping platform. The implementation method included socialization, pre- and post-tests, training, hands-on practice, and mentoring for one month to ensure the sustainability of the material implementation. Evaluation used a 1–5 scoring scale (1 = very low, 5 = very high). The results of the activity showed a significant increase in competency, marked by an increase in the average score from 3.1 to 4.4, an increase of 1.3 points (41.9%). In addition, there was an increase in business performance with an increase in sales transactions from 11 transactions in August to 27 transactions in September after the digital marketing strategy was consistently implemented. This program has resulted in improved digital literacy, managerial skills, and expanded partner market reach. Furthermore, it also strengthens circular economy practices by utilizing shellfish waste into value-added products and provides contextual learning experiences for students in mentoring technology-based MSMEs.